(untitled) (Herald of Journalism, 2016)
The article examines the relationship of show business with mass culture and mass media. It is attempt to consider the characteristics of entertainment art and its influence on the modern world and the consciousness of people. The authors conclude that the modern Kazakh show business – is, above all, the commercial sector for the creation and dissemination of mass entertainment or representation influencing human senses, aimed at the rapid movement of goods and services, political, intellectual or artistic nature.